Teenage sexuality: opposing viewpoints - Bernards, Neal (Opposing viewpoints series, 1988)
Presents opposing viewpoints about teenage attitudes toward sex, their sexual and reproductive rights, teenage pregnancy, sex education, and school-based clinics